The tax consequences of the transfer of technical reserves between short-term insurers as part of a portfolio transfer - Griessel, Jolandi (Department of Finance and Tax, 2021)
This dissertation focusses on the tax implications of a portfolio transfer between short-term insurers. The commercial purpose of a portfolio transfer is for one insurer (‘transferee') to effectively take over the insurance policies of another insurer (‘transferor'), with no negative impact on the interest of the policy holders. In order to effect a portfolio transfer, the technical reserves recognised by the transferor in its Annual Financial Statements (‘AFS') are transferred to the transferee along with the working capital backing these reserves. The working capital is essentially an amount of cash and other liquid assets equal to the net technical reserve value. The research question that is addressed by this dissertation is: Does the current income tax legislation sufficiently address the tax consequences of the transfer of technical reserves and working capital between short-term insurers as part of a portfolio transfer to yield a fair and reasonable result from a tax perspective? In addressing the research question the dissertation analyses the nature of technical reserves from an accounting and regulatory perspective and considers the tax treatment thereof under the provisions of section 28 of the Income Tax Act No. 58 of 1962 (‘IT Act'), which deals with the taxation of short-term insurance business. It considers the tax implications of a portfolio transfer of technical reserves from both the perspective of the transferor and the transferee and considers international practise in this regard. This dissertation concludes that although the working capital will be included in the taxable income of the transferee (purchaser) there will not necessarily be a deduction from taxable income available for the transferor (seller). The transfer of technical reserves and working capital does not result in a profit or loss for either the transferor or the transferee and consequently such a transfer would be expected to be tax neutral. The tax treatment is therefore not in line with the commercial purpose of a portfolio transfer. Amendments to section 28 are thus required to specifically confirm that a deduction of the working capital will be available for the transferor (seller) and that the amount be included in the income of the transferee (purchaser) as this will create certainty and avoid inconsistent results from a tax policy perspective, especially given the significant values involved in these transactions.